Sustainability of Paddy Rice Farming in the Conservation of Birds in Uganda Amidst a Growing Expansion of the Rice farming Industry. - Sarah, Nachuha; Twagiramaria, Fortunate (Kabale University, 2023)
Rice has become a cash crop in Uganda, making the rice agro-ecosystems a common feature in ecological landscapes. In this research, waterbird species diversity at three paddy rice growing schemes namely: Doho, Kibimba and Lukaya is collected and compared. A rapid cross-sectional survey was conducted at these 3 sites over a period of 3 months in which both quantitative and qualitative data were collected. This study was guided by the anthropogenic impacts hypothesis which proposes that humans have modified the ‘natural’ biodiversity patterns such that diversity is generally depressed in areas with long history of human occupation or intensive activities. Results of One-way ANOVA show significant variations in species diversity (P = 0.022) and abundance (P=0.04) across the sites. There was generally a low diversity at the sites. However, Doho rice scheme had the highest waterbird diversity (1.05±0.99), followed by Kibimba (0.09±0.05) while Lukaya had the least (0.07±0.02), and the reverse was true for waterbird abundance. Birds of international significance such as the Grey crowned Crane (Balearica regulorum) were more abundant at Lukaya Rice scheme than the other two. Kibimba and Doho rice rich schemes have been under rice cultivation for almost 5 decades while Lukaya rice fields are hardly a decade old. The findings are contrary to the hypothesis; most probably because rice fields are artificial habitats that are attractive to water birds only when there are farming activities going on. Out of the 150 farmers we interacted with, 120 (80%) mentioned that the Grey crowned Crane (Balearica regulorum) numbers had declined, mainly because of conversion of the natural wetland into rice paddies, moreover the birds on the paddies are also threatened by extensive use of pesticides and herbicides, including hunting by the local community members. There is need to introduce alternative income-generating activities and continuous sensitization of stakeholders on wise use of rice farms.